Pengaruh Gaya Kepemimpinan Otoriter Terhadap Motivasi Karyawan di Kafe Riverside - Siahaan, Agustinus; Dalimunthe, Hairul Anwar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Leadership style is an important factor influencing employee work motivation. This study aims to analyze the effect of authoritarian leadership style on the work motivation of employees in a café. The research employed a quantitative approach with a survey method, where data were collected through questionnaires completed by active employees. Data analysis was conducted using simple regression to examine the relationship between the two variables. The results show a regression coefficient of β = -0,487, a t-value = -3.582, and a p-value = 0.001 (< 0.05), indicating that authoritarian leadership style has a negative and significant effect on employee work motivation. The coefficient of determination (R²) of 0.258 indicates that 25.8% of the variation in employee work motivation can be explained by the authoritarian leadership style, while the remaining 74.2% is influenced by other factors outside the research model. These findings emphasize that the application of an overly authoritarian leadership style can hinder participation, engagement, and employee morale, ultimately leading to decreased job satisfaction.